Financial Administration System in Document Management and Transaction Data at PT Dimensi Citra Semesta - Nugroho, Rusdi; Balqis, Amalia (Indonesian Journal Publisher, 2026)
This study aim For describe How management finance done For recording and information sales at PT Dimensi Citra Semesta . The method used is with observe in a way carefully, with example studies that include observation direct, collection documents, and help moment internship. This study show that use system management finance based computer help speed up recording, making it easier recording, and reducing risk error information. Although however, still There is room For repair in matter How system the Work The same with other things and how much appropriate performance employee in manage finance.